2005
DOI: 10.1128/jvi.79.4.2432-2439.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Dengue Virus on Infected and Bystander Dendritic Cells

Abstract: Dendritic cells (DCs) play a central role as major targets of dengue virus (DV) infections and initiators of antiviral immune responses. Previous observations showed that DCs are activated by infection, presumablyacquiring the capacity to promote cell-mediated immunity. However, separate evaluations of the maturation profiles of infected and uninfected bystander cells show that infection impairs the ability of DCs to upregulate cell surface expression of costimulatory, maturation, and major histocompatibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
107
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(140 citation statements)
references
References 44 publications
(60 reference statements)
25
107
1
7
Order By: Relevance
“…Indeed, TNF-α and IFN-α can have adverse effects when produced in huge amounts after viral infection [32]. Thus, it was suggested that TNF-α secreted by CD172a + cells, together with IL-1, IL-6 and prostaglandin, were responsible for apoptosis in non-infected immune system cells in lymphoid organs [16,24,38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TNF-α and IFN-α can have adverse effects when produced in huge amounts after viral infection [32]. Thus, it was suggested that TNF-α secreted by CD172a + cells, together with IL-1, IL-6 and prostaglandin, were responsible for apoptosis in non-infected immune system cells in lymphoid organs [16,24,38].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, algunos autores describen que la activación de las DC infectadas es menor, comparada con la activación de células adyacentes no infectadas 36,37 . Dado que las imDC infectadas con DENV presentan un menor grado de maduración, comparado con imDC adyacentes no infectadas, se ha propuesto que la infección de las DC tiene un efecto directo en la expresión de moléculas co-estimuladoras , lo que conllevaría a la activación de las DC adyacentes 55 . Esto podría estar relacionado con la apoptosis observada en DC infectadas por DENV, consecuencia de la replicación viral, lo que a la vez podría estar relacionado con la patogénesis del dengue 55,56 .…”
Section: Consecuencias De La Infección De DC Por Denvunclassified
“…Dado que las imDC infectadas con DENV presentan un menor grado de maduración, comparado con imDC adyacentes no infectadas, se ha propuesto que la infección de las DC tiene un efecto directo en la expresión de moléculas co-estimuladoras , lo que conllevaría a la activación de las DC adyacentes 55 . Esto podría estar relacionado con la apoptosis observada en DC infectadas por DENV, consecuencia de la replicación viral, lo que a la vez podría estar relacionado con la patogénesis del dengue 55,56 . Otro aspecto importante a tener presente al momento de establecer los mecanismos implicados en la patogénesis del DENV y el papel de las DC en dicho proceso, es la expresión de metalo-proteinasas de matrix (sigla en inglés MMP), como MMP-2, MMP-9 y MMP-13.…”
Section: Consecuencias De La Infección De DC Por Denvunclassified
See 2 more Smart Citations